The European regional crime database: data from the book "Crime in Europe" - Entorf, Horst; Spengler, Hannes (Darmstadt discussion papers in economics, 2004)
This paper contains a documentation of the EU regional crime database (EURCD). The EURCD is the basis of the analyses presented in our recently published book 'Crime in Europe' which, in turn, is the result of a research project conducted on behalf of the EU Commission. The EURCD is a panel dataset containing information on 12 Interpol crime categories (murder, sex offences, rape, serious assault, theft, aggravated theft, robbery and violent theft, breaking and entering, theft of motor cars, fraud, drug offences and total offences) across eight EU member states (Denmark, Germany, Spain, Italy, the Netherlands, Finland, Sweden and England & Wales) for the maximal period 1980-1998 (length of period depends on country and region). The spatial structure of the EURCD is organised according to Eurostat's NUTS-system, meaning that it contains data broken down into, for instance, German 'Kreise', Spanish 'Provincias' and Italian 'Provincias'. Crime data obtained for countries which, for reasons explained in the paper, could not (Belgium, Greece, Portugal) or only partly (England & Wales) be integrated into the analyses is (or will soon be) provided in country-specific files. There is a lack of data for Ireland and Luxemburg because regional crime data does not exist for these countries, and for France and Austria which refused to participate in the project. In order to allow multivariate analyses of the causes and consequences of crime the EURCD also contains a sizeable number of non-crime variables. By providing this data to the public we hope to enhance empirical crime research in Europe which until today has been denied adequate attention by both criminologists and economists.